Os determinantes socioeconômicos da obesidade infantojuvenil no Brasil - Valle, Sinara do (2021)
This work aims at analyzing the socioeconomic determinants of obesity among youths in Brazil. By making use of the Brazilian Family Budget Survey (POF) microdata, a quantile regression with separation by income classes and macro-regions is applied. The variables used are: body mass index (BMI) for children and adolescents, household income per capita, education and obesity status of the family, gender, location of the household (urban or rural area), sanitation conditions, durable goods in the residence. The macro-regions considered are dichotomized in Center-South and North-Northeast. The results show that factors, such as higher income level, obesity of the head of household, households located in the urban area are positively related to youth obesity. On the other hand, there is a decrease in the proportion of overweight children and adolescents in households where the head is well-educated and participants of the Bolsa Família Program.The effects of changes in the abovementioned lags on childhood and adolescent obesity are more exacerbated in the higher strata of per capita family income and in the Center-South macro-region. On the other hand, there is a significant negative effect on childhood and youth obesity in households with lack of basic sanitation and with fewer durable consumer goods. The greatest magnitude occurs among the poorest and in the North-Northeast macro-region. Thus, childhood and youth obesity, can be seen as a way of perpetuating poverty, since it can negatively impact the country’s economic development. Thus, it is concluded that the observed prevalences of overweight and obesity in childhood and adolescence justify the importance of national and regional goals with a time limit for the reduction of childhood and adolescent obesity, accompanied by detailed action plans and monitoring mechanisms.